Prevalence of Professional Misconduct in Nzega District, Tanzania Public Secondary Schools - Stephen Mabagala (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2017)
The purpose of this study was to investigate the prevalence of professional misconduct among public secondary school teachers in Nzega District, Tanzania public secondary schools. This study employed descriptive survey research design. The sample consisted of 403 respondents in which teachers and students were randomly selected, while heads of schools and Teachers Services Department (TSD) officials were purposively selected based on their administrative roles. Data for this study were collected through questionnaire and semi-structured interview guide. Data were analyzed using descriptive statistics using SPSS version 20. Findings revealed that teachers' professional misconduct was low. However, financial mismanagement, negligence of duty, and absenteeism were among the common professional misconduct acts in secondary schools in Nzega District. Findings also revealed that, poor remuneration, failure to fulfill teachers' needs, and lack of motivation were among the sources of teacher's explanations for misconduct. Based on the findings, the government through the Ministry of Education and Vocational Training (MoEVC) should respond to teachers' needs in a timely manner, and conduct regular seminars on teacher professionalism. Moreover, a similar study should be conducted to assess teachers' misconduct at primary school and higher institution levels.